PENGARUH PENGGUNAAN PENDEKATAN VALUE CLARIFICATION TECHNIQUE (VCT) METODE PERCONTOHAN TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN DI SEKOLAH DASAR - Halimatun Sakdiah; Reinita Reinita (Jurnal Bahana Manajemen Pendidikan, 2019)
This study aims to determine the effect of  Value Clarification Technique (VCT) modeling method on the studnts’ learning outcome in civic education. This study is a quasi-experimental design with a non-equivalent control group. The research was conducted in cluster VI elementary school akabiluru sub-district district fifity cities. Sampling data is taken by purposive sampling. The sample of this study amounted to 40 people, with a population of 92 people. Based on the research that has been done, obtained t count> t table, 1,98 >1,72 with α = 0.05 is means Ho is rejected and Ha accepted. Therefore, it is concluded that the Value Clarification Technique modeling method affects the students’ learning outcome in civic education in cluster VI elementary school akabiluru sub-district district fifity cities.